Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Let's solve each of the four given equations step-by-step to find the value of [tex]\( x \)[/tex].
### Solve the first equation:
[tex]\[ 8.3 = -0.6x + 11.3 \][/tex]
1. Subtract 11.3 from both sides:
[tex]\[ 8.3 - 11.3 = -0.6x \][/tex]
[tex]\[ -3 = -0.6x \][/tex]
2. Divide by -0.6:
[tex]\[ x = \frac{-3}{-0.6} \][/tex]
[tex]\[ x = 5 \][/tex]
### Solve the second equation:
[tex]\[ 11.3 = 8.3 + 0.6x \][/tex]
1. Subtract 8.3 from both sides:
[tex]\[ 11.3 - 8.3 = 0.6x \][/tex]
[tex]\[ 3 = 0.6x \][/tex]
2. Divide by 0.6:
[tex]\[ x = \frac{3}{0.6} \][/tex]
[tex]\[ x = 5 \][/tex]
### Solve the third equation:
[tex]\[ 11.3 - 0.6x = 8.3 \][/tex]
1. Subtract 8.3 from both sides:
[tex]\[ 11.3 - 8.3 - 0.6x = 0 \][/tex]
[tex]\[ 3 = 0.6x \][/tex]
2. Divide by 0.6:
[tex]\[ x = \frac{3}{0.6} \][/tex]
[tex]\[ x = 5 \][/tex]
### Solve the fourth equation:
[tex]\[ 8.3 - 0.6x = 11.3 \][/tex]
1. Subtract 8.3 from both sides:
[tex]\[ 8.3 - 8.3 - 0.6x = 11.3 - 8.3 \][/tex]
[tex]\[ -0.6x = 3 \][/tex]
2. Divide by -0.6:
[tex]\[ x = \frac{3}{-0.6} \][/tex]
[tex]\[ x = -5 \][/tex]
### Conclusion
The first three equations:
[tex]\[ 8.3 = -0.6x + 11.3 \][/tex]
[tex]\[ 11.3 = 8.3 + 0.6x \][/tex]
[tex]\[ 11.3 - 0.6x = 8.3 \][/tex]
all yield the solution:
[tex]\[ x = 5 \][/tex]
The fourth equation:
[tex]\[ 8.3 - 0.6x = 11.3 \][/tex]
yields a different solution:
[tex]\[ x = -5 \][/tex]
Therefore, the equation that results in a different value of [tex]\( x \)[/tex] than the other three is:
[tex]\[ 8.3 - 0.6x = 11.3 \][/tex]
### Solve the first equation:
[tex]\[ 8.3 = -0.6x + 11.3 \][/tex]
1. Subtract 11.3 from both sides:
[tex]\[ 8.3 - 11.3 = -0.6x \][/tex]
[tex]\[ -3 = -0.6x \][/tex]
2. Divide by -0.6:
[tex]\[ x = \frac{-3}{-0.6} \][/tex]
[tex]\[ x = 5 \][/tex]
### Solve the second equation:
[tex]\[ 11.3 = 8.3 + 0.6x \][/tex]
1. Subtract 8.3 from both sides:
[tex]\[ 11.3 - 8.3 = 0.6x \][/tex]
[tex]\[ 3 = 0.6x \][/tex]
2. Divide by 0.6:
[tex]\[ x = \frac{3}{0.6} \][/tex]
[tex]\[ x = 5 \][/tex]
### Solve the third equation:
[tex]\[ 11.3 - 0.6x = 8.3 \][/tex]
1. Subtract 8.3 from both sides:
[tex]\[ 11.3 - 8.3 - 0.6x = 0 \][/tex]
[tex]\[ 3 = 0.6x \][/tex]
2. Divide by 0.6:
[tex]\[ x = \frac{3}{0.6} \][/tex]
[tex]\[ x = 5 \][/tex]
### Solve the fourth equation:
[tex]\[ 8.3 - 0.6x = 11.3 \][/tex]
1. Subtract 8.3 from both sides:
[tex]\[ 8.3 - 8.3 - 0.6x = 11.3 - 8.3 \][/tex]
[tex]\[ -0.6x = 3 \][/tex]
2. Divide by -0.6:
[tex]\[ x = \frac{3}{-0.6} \][/tex]
[tex]\[ x = -5 \][/tex]
### Conclusion
The first three equations:
[tex]\[ 8.3 = -0.6x + 11.3 \][/tex]
[tex]\[ 11.3 = 8.3 + 0.6x \][/tex]
[tex]\[ 11.3 - 0.6x = 8.3 \][/tex]
all yield the solution:
[tex]\[ x = 5 \][/tex]
The fourth equation:
[tex]\[ 8.3 - 0.6x = 11.3 \][/tex]
yields a different solution:
[tex]\[ x = -5 \][/tex]
Therefore, the equation that results in a different value of [tex]\( x \)[/tex] than the other three is:
[tex]\[ 8.3 - 0.6x = 11.3 \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.